Formulation and In vitro Characterization of Phenytoin Loaded Mucoadhesive Biofilms of Colocasia esculenta for Translabial Drug Delivery System - Ojha, Abhijeet; Madhav, NV Satheesh (Dhaka University Journal of Pharmaceutical Sciences, 2017)
The aim of our research work was to isolate a biomaterial from Colocasia. esculenta and prepare phenytoin loaded mucoadhesive biofilms using this biomaterial. The biomaterial was isolated from C. esculenta tubers by an economical process. The isolated biomaterial was subjected to various physical evaluation, chemical tests as well as spectral analysis. The drug-biomaterial interaction study was performed to see if there was any interaction of biomaterial with phenytoin. Phenytoin loaded biofilms were prepared using biomaterial, flexicizer and other co- processing agents. The prepared biofilms were evaluated for physical appearance, weight, thickness, folding endurance, swelling index, surface pH, tensile strength, percent elongation, percent moisture uptake, percent moisture loss, vapor transmission rate and content uniformity. The mucoadhesivity of biofilms was investigated using rotating basket method. The in-vitro drug release study of biofilms was performed on static MS diffusion apparatus. The stability studies of biofilms were carried out at different conditions of temperature and relative humidity. The results were compared with the standard hydroxy propyl methyl cellulose (HPMC) and sodium carboxymethyl cellulose (Sodium CMC) films. The experimental results revealed that the phenytoin loaded biofilms of C. esculenta possessed excellent mucoadhesivity, sufficient stability as well as appreciable release characteristics. The best biofilm formulation was PK6 with a cumulative drug release of 95.35 % over 36 hours. Hence, C. esculenta biomaterial can serve as a potential film forming agent for transmucosal drug delivery systems. Dhaka Univ. J. Pharm. Sci. 15(2): 177-186, 2016 (December)